The Influence of Career Development and Organizational Culture on Employee Satisfaction Institutions Public Broadcasting TVRI West Kalimantan - Resky Hartanty; Irfan Mahdi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Human Resource Management plays a crucial role in determining organizational success, as organizational performance is highly influenced by the quality and contributions of employees. Employees are not only implementers but also key drivers in achieving organizational goals. Job satisfaction is an important factor affecting employee discipline, attendance, and work motivation. In addition, career development and a strong organizational culture contribute to creating a supportive work environment that enhances both performance and job satisfaction. In public broadcasting institutions such as TVRI, the professionalism and quality of human resources are essential in delivering information, education, and entertainment to the public. TVRI West Kalimantan, as part of this institution, faces challenges in implementing organizational culture, including gaps between expected values and actual employee behavior, particularly in terms of discipline and responsibility. Furthermore, leadership changes require employees to adapt to new policies and working styles. Previous studies indicate that organizational culture and career development have a positive and significant influence on job satisfaction, which in turn improves employee performance. Therefore, it is important for organizations to strengthen a positive work culture and provide career development opportunities in order to enhance employee satisfaction and performance effectively.